Strategies to optimize siRNA delivery to hepatocellular carcinoma cells - Scarabel, Lucia; Perrone, Francesca; Garziera, Marica; Farra, Rossella; Grassi, Mario; Musiani, Francesco; Russo Spena, Concetta; Salis, Barbara; De Stefano, Lucia; Toffoli, Giuseppe; Rizzolio, Flavio; Tonon, Federica; et al. (Expert opinion on drug delivery, 2017)
hepatocellular carcinoma (hcc) is the predominant form of primary liver cancer and the second leading cause of cancer-associated mortality worldwide. available therapies for hcc have limited efficacy due to often late diagnosis and the general resistance of hcc to anti-cancer agents; therefore, the development of novel therapeutics is urgently required. small-interfering rna (sirna) molecules are short, double-stranded rnas that specifically recognize and bind the mrna of a target gene to inhibit gene expression. despite the great therapeutic potential of sirnas towards many human tumors including hcc, their use is limited by suboptimal delivery. Areas covered: In this review, we outline the current data regarding the therapeutic potential of siRNAs in HCC and describe the development of effective siRNA delivery systems. We detail the key problems associated with siRNA delivery and discuss the possible solutions. Finally, we provide examples of the various siRNA delivery strategies that have been employed in animal models of HCC and in human patients enrolled in clinical trials. Expert opinion: Despite the existing difficulties in siRNA delivery for HCC, the increasing scientific attention and breakthrough studies in this field is facilitating the design of novel and efficient technical solutions that may soon find practical applications.
Keywords: nádory jater; Humans; drug delivery; Antineoplastic Agents; lidé; liposome; Liver Neoplasms; zvířata; buněčné linie; RNA, Small Interfering; malá interferující RNA; Cell Line; hepatocellular carcinoma; protinádorové látky; polymers; Animals; siRNA; Carcinoma, Hepatocellular; hepatocelulární karcinom